Transcriptional diversity of the oxytocin receptor in prairie voles: mechanistic implications for behavioral neuroscience and maternal physiology - Danoff, Joshua S.; Page, Emma A.; Perkeybile, Allison M.; Kenkel, William M.; Yee, Jason R.; Ferris, Craig F.; Carter, C. Sue; Connelly, Jessica J. (Frontiers in Genetics, 2023)
The neurohormone oxytocin regulates many aspects of physiology primarily by binding to its receptor, the oxytocin receptor. The oxytocin receptor gene (Oxtr) has been shown to have alternative transcripts in the mouse brain which may each have different biological functions or be used in specific contexts. A popular animal model for studying oxytocin-dependent social behaviors is the prairie vole, a biparental and monogamous rodent. Alternative transcriptional capacity of Oxtr in prairie voles is unknown. We used 5′ rapid amplification of cDNA ends to identify alternative Oxtr transcription start sites in prairie vole brain tissue and uterine tissue. We then validated expression of specific transcripts in fetal brains and assessed the impact of exogenous oxytocin administration in utero on offspring brain development. We identified seven distinct Oxtr transcripts, all of which are present in both brain and uterine tissue. We then demonstrated that maternal oxytocin administration alters expression of a specific subset of Oxtr transcripts and that these different transcripts are under unique epigenetic regulation, such that in the perinatal period only one of the alternative transcripts is associated with DNA methylation in the Oxtr promoter. These data establish the existence of multiple Oxtr transcripts in prairie vole brain and uterine tissue and implicate oxytocin in the regulation of alternative transcript expression. These data have significant implications for our understanding of null mutant models in both mice and voles and translation in human birth and behavior.